Design Guidelines for Micro‐Thermoelectric Devices by Finite Element Analysis. (9th January 2019) - Lara Ramos, David Alberto; Barati, Vida; Garcia, Javier; Reith, Heiko; Li, Guodong; Pérez, Nicolás; Schierning, Gabi; Nielsch, Kornelius
Abstract: Energy harvesting and thermal management are required for applications in the internet‐of‐things, autarkic sensors, or highly integrated electronic devices. Thermoelectric devices, both generators and coolers, are promising specialized technologies for localized energy harvesting and thermal management. These devices are well optimized for near‐room temperature operation at the macroscopic scale. However, the high integration density of today's most significant applications requires an increasing degree of miniaturization. Understanding the design guidelines for micro‐thermoelectric devices with realistic materials properties, and with concurring size and geometry constraints, is a challenge that has not been fully addressed up to now. Here, finite element analysis is used to understand the interplay between thermal and electrical heat fluxes in micro‐thermoelectric devices. The relevant design guidelines for metallic top and bottom contacts and thermoelectric elements, as well as an optimal packing density of the thermoelectric elements are identified. The results demonstrate that on the micrometer scale, the effects of net electrical and thermal resistances of the individual components of the devices (i.e., thermoelectric leg, top, and bottom contacts) are of comparable magnitude. This makes it necessary to apply design strategies specific to the micrometer scale, in order to geometrically optimize the device. Abstract : The harvesting of energy and the thermal management for electronic devices is of prime importance. This can be achieved by the integration of micro‐thermoelectric devices. Here the relevant design guidelines for the micro‐thermoelectric devices are identified including the geometric arrangement of the thermoelectric materials and metallic top and bottom contacts by finite element simulation.